1406. IMPACT (Infection Management Plus Addiction Care Together): A Combined Contingency Management Pilot for Substance Use Disorders & Antibiotic Adherence in the Acute Care Setting. (15th December 2022) - Appa, Ayesha Ashley; Stein, Brianna; Baral, Stefan; Knight, Kelly; Gandhi, Monica; Coffin, Phillip; Martin, Marlene
Abstract: Background: Amidst interrelated problems of increasing infections related to drug use and overdose deaths, contingency management (CM) is an underutilized substance use disorder treatment that leverages incentives for objective behavior change. CM implementation outside of drug treatment settings is limited, despite its regard as gold-standard treatment for stimulant use disorder and potential use to support infection treatment completion. Objective: to describe feasibility and preliminary effectiveness of a novel CM program incentivizing reduced drug use and antibiotic adherence in the acute care setting. Methods: We conducted a pilot of twice weekly CM in an urban public hospital and its attached skilled nursing facility with escalating opportunities to earn incentives from a fishbowl based on 1) antibiotic adherence and/or 2) absence of stimulants or opioids on urine drug testing. Eligible participants were people with stimulant and/or opioid use disorders hospitalized for at least 2 weeks of infection treatment. We measured feasibility via visits attempted/completed and cost of gift cards dispensed. We evaluated effectiveness via antibiotic completion, discharge type, and participant perception of intervention effectiveness collected via structured survey. Results: Between March-April 2022, n=9 participants were referred to IMPACT, and n=7 were enrolled. Most participants (5/7) required antibiotics for osteomyelitis, and most had stimulant use disorder (methamphetamine, 5/7) and opioid use disorder (fentanyl, 5/7). In 4 of 7 instances, multiple visits were necessary to complete a CM visit, and participants earned between $10-$350 during intervention. Only 1 participant self-directed discharge without antibiotic completion. Most participants reported CM "extremely effective" in supporting antibiotic completion, though were more likely to describe CM as moderately effective (range 5-8/10) in addressing drug use reduction. Conclusion: CM for patients with stimulant and/or opioid use disorders needing prolonged antibiotics in acute care settings may be effective in supporting antibiotic completion, and additional exploration is needed to understand both program feasibility and its role in supporting reduced drug use for participants after discharge. Disclosures: All Authors : No reported disclosures.